2022
DOI: 10.1097/acm.0000000000004709
|View full text |Cite
|
Sign up to set email alerts
|

Social Support, Social Isolation, and Burnout: Cross-Sectional Study of U.S. Residents Exploring Associations With Individual, Interpersonal, Program, and Work-Related Factors

Abstract: Purpose To examine associations of social support and social isolation with burnout, program satisfaction, and organization satisfaction among a large population of U.S. residents and fellows and to identify correlates of social support and social isolation. Method All residents and fellows enrolled in graduate medical education programs at Mayo Clinic sites were surveyed in February 2019. Survey items measured social support (emotional and tangible), social isolation, burnout, program satisfaction, and orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…In a cross-sectional study of US resident physicians, increased social isolation was associated with higher odds of burnout and lower odds of program satisfaction and organization satisfaction. 19 The clear message is that hospitals, healthcare systems, and those involved in neurosurgical resident education must understand the costs of burnout, recognize its signs in staff, and have policies and programs in place to address it. It is possible, however, that these results reflect individual reprioritization as a consequence of the events and experience of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of US resident physicians, increased social isolation was associated with higher odds of burnout and lower odds of program satisfaction and organization satisfaction. 19 The clear message is that hospitals, healthcare systems, and those involved in neurosurgical resident education must understand the costs of burnout, recognize its signs in staff, and have policies and programs in place to address it. It is possible, however, that these results reflect individual reprioritization as a consequence of the events and experience of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…There is compelling evidence that a focus on social support and social connection may help us address this problem. A survey of all residents and fellows at the Mayo clinic reported that the odds of burnout decreased 45% for each 1-point increase in an emotional support score and more than tripled for every 1-point increase in the social isolation score 31 . A survey of surgical residents and faculty across seven institutions reported that struggling to find a mentor and lack of a social community outside of work were primary factors associated with burnout 32 .…”
Section: The Importance Of Social Connection In Caring For Each Othermentioning
confidence: 99%
“…A survey of all residents and fellows at the Mayo clinic reported that the odds of burnout decreased 45% for each 1-point increase in an emotional support score and more than tripled for every 1-point increase in the social isolation score. 31 A survey of surgical residents and faculty across seven institutions reported that struggling to find a mentor and lack of a social community outside of work were primary factors associated with burnout. 32 A similar relationship has also been described in the nursing literature with a systematic review including 24 studies, which found an inverse relationship between social support and burnout and suggested that social support may account for up to one third of the variation in burnout.…”
Section: The Importance Of Social Connection In Caring For Each Othermentioning
confidence: 99%
“…This may equate to exhaustion and reduced cognitive performance, and consequently, to emotional distancing and indifference towards one's profession, as a self-defense coping mechanism [32][33]. In addition, working outside conventional daytime hours, including night work, or high rotation shifts, can also trigger key features of burnout, such as feelings of depersonalization, depletion, loneliness, or disconnection [34]. This mainly stems from the disruption of circadian rhythms and sleep-wake patterns, associated with physiocognitive recovery [35][36], as well as from the social isolation and work-life imbalance, correlated with overnight working and daytime sleeping [37][38].…”
Section: Introductionmentioning
confidence: 99%